Manual de control interno para mejorar la gestión financiera de la caja solidaria "nueva vida" comunidad curiquingue, Parroquia Pastocalle, Cantón Latacunga - Ganazhapa Guamán, Evelyn Thalía (2019)
Internal control has played an essential role within financial entities, which have established norms and regulations that contribute to demonstrate the efficiency of their management regarding the fulfillment of the organizational objectives which generates a higher level of security. Nowadays, "Nueva Vida" Basket Fund is the responsibility of Latacunga Canton, Pastocalle Parish, Curiquingue Community, and provides money collection services and the granting of easy and timely loans. It has two collaborators who carry out various activities without having internal procedures or controls to assist the correct development of the entity; so there is inadequate control in financial management; and for that reason, this project addresses the development of an internal control manual that helps strengthen processes. The methodologies used during the execution of this project were the documentary and field ones, the applied techniques such as the observation and the questionnaire were based on the COSO II in order to obtain relevant and objective information for its development. It is necessary for the entity to have appropriate internal control that will optimize the use of resources and safeguard its assets that reduces the inherent risk. The proposed manual establishes policies, functions, and procedures that will contribute to the proper development of the activities carried out by the Basket Fund in an efficient way, strengthening its financial processes for taking timely decisions, thereby obtaining a high degree of reliability and achieving compliance with his objectives that will help the socioeconomic development and provide quality services to its partners; therefore the entity has a better organizational control, generates more liquidity and can take actions to mitigate administrative and financial risks that may arise.